Built Environment and Preterm Birth - Woods, Nikki Keene; Watson, Linda; Nguyen, An-Diep T (Kansas Journal of Medicine, 2014)
Background. Preterm birth affects approximately 500,000 babies a year in the United States. One out of nine babies born in the United States deliver before 37 weeks gestation. Preterm birth can cause lifelong neurological problems, cerebral palsy, vision and hearing impairments, and developmental delay. The estimated $26 billion a year in preterm birth related costs are staggering to the health care system. Preterm-related causes of death in 2008 together accounted for 35% of all infant deaths. Methods. This paper is a review of the literature published (2006-2012) on the relationship between neighborhood environment and preterm birth. Results. Neighborhood deprivation and the neighborhood environment were associated with low-birth weight and preterm birth. Examples of neighborhood deprivation include economic deprivation, social disorder, and lack of health resources. Neighborhood environment can be described as neighborhood physical deterioration, violent crime, and group density. Conclusions. A significant association exists between the neighborhood environment and birth outcomes. More research is needed to explore interventions with a systems approach to promote healthy maternal behavior, reduce stress, and improve care for expecting mothers living in stressful neighborhood environments in order to reduce preterm births.